2014
DOI: 10.5935/medicalexpress.2014.03.06
|View full text |Cite
|
Sign up to set email alerts
|

Protective microcirculatory and anti-inflammatory effects of heparin on endotoxemic hamsters

Abstract: OBJECTIVE: Apart from its anticoagulant properties, heparin has vasodilator and anti-inflammatory effects that could assist in the reversal of septic microcirculatory changes. This paper investigates the effects of heparin on endotoxemia-related microcirculatory changes and compares them to those observed with the use of recombinant human activated protein C. METHODS: After skinfold chamber implantation procedures and endotoxemia induction by intravenous Escherichia coli lipopolysaccharide administration (2 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…ingly, microcirculatory recruitment appeared to be independent of the anticoagulant effects of these drugs (6,10,54,64,80). Despite microvascular improvement, none of these agents have consistently improved the outcome of septic patients in numerous clinical trials, but all significantly increased the risk of bleeding (44,80). Activated protein C was withdrawn from markets worldwide in the wake of a clinical trial showing that, compared with placebo, this agent did not significantly reduce mortality in patients with septic shock (89).…”
Section: No Synthase Modulationmentioning
confidence: 99%
“…ingly, microcirculatory recruitment appeared to be independent of the anticoagulant effects of these drugs (6,10,54,64,80). Despite microvascular improvement, none of these agents have consistently improved the outcome of septic patients in numerous clinical trials, but all significantly increased the risk of bleeding (44,80). Activated protein C was withdrawn from markets worldwide in the wake of a clinical trial showing that, compared with placebo, this agent did not significantly reduce mortality in patients with septic shock (89).…”
Section: No Synthase Modulationmentioning
confidence: 99%
“…These results provide evidence that WW-85 blocks NO production, thereby improving cardiovascular function and microcirculation. Miranda et al [ 42 ] investigated the effects of heparin on endotoxemia-related microcirculatory changes and compared them to those observed with the use of recombinant human activated protein C. Heparin decreased lipopolysaccharide-induced leukocyte rolling and arteriolar vasoconstriction; survival increased in treated vs. non-treated animals. Administration of heparin plus recombinant human activated protein C was associated with a significant attenuation of lipopolysaccharide-induced capillary perfusion deficits.…”
Section: Resultsmentioning
confidence: 99%
“…Several animal and human studies have suggested that heparin not only effectively prevents the coagulation mechanism in endotoxaemia, but also causes a variety of anti-inflammatory responses against infection. Human endotoxaemia experimental models have indicated that heparin can treat endotoxaemia by inducing coagulation activities (Jaimes et al, 2006;Li et al, 2009;Li et al, 2013;Miranda et al, 2014;Schiffer et al, 2002;Wyns et al, 2015;Zhao et al, 2017). However, in human models, the inhibition of inflammatory pathways following endotoxaemia has not been as clearly demonstrated as in animal Several animal and human trials have been conducted to investigate the possible benefits of heparin in the treatment of bacterial infections.…”
Section: Discussionmentioning
confidence: 99%